Education and Training Center for Youth with Multisensory Design Approach - Ghazali, Achmad Ramzy Arighi; Ekasiwi, Sri Nastiti Nugrahani; Noerwasito, Vincentius Totok (Institut Teknologi Sepuluh Nopember, 2020)
Lack of education and training facilities for youth people who are in accordance with the visual learner's learning system makes one aspect of the lack of interest of youth in developing and increasing their productivity. Therefore, this research is conducted to provide an architectural concept that can adapt to the visual learner's learning system for youth. The design concept of the design uses a multisensory theory approach to create attention, sensation and memory into the visual learner learning system for youth. In addition, the direct analogy approach to visual functions becomes one of the design strategies to give attention especially youth in better understanding the stages to be carried out, namely the professionalism stage. Architectural factors that influence the productivity of youth are the shape, scale, color, and materials used in rooms and buildings. This was obtained by means of observation and participatory questionnaires with youth of productive age. Besides the professionalism factors that can assess the productivity of youth are knowledge, skills, and attitude. This was obtained by the questionnaire method with the HRD manager. The method used in the idea uses the concept base framework design method. To present a moment in the design framework, it is necessary to have a research method in it, namely participatory qualitative methods, literature observation and environmental mapping on selected land. The moment presented will limit the exploration of elements that have a role in increasing visual perception in youth’s productivity. Moment will evaluate architectural factors that can be adapted to existing environmental conditions, so as to create the perfect concept in increasing the productivity of youth.